Fingerprint Characteristics of North Poland Population - Buchwald, Wiesław (Anthropological Review, 1981)
Dermatoglyphes of fingers were observed in a sample of 1234 males and females living in a Northern part of Poland. Fingerprint characteristics were classified qualitatively according to the Lestrange-Bocheńska system. Frequencies of patterns and their directions are given in table 2 for males and in table 3 for females. Frequencies of the three main pattern categories (arches, loops and whorls) — table 4 — were used for stati-stical assesment of sexual dimorphism (table 5) and regional variability. Pattern frequencies: A — 6.4%, L — 63.4%, W — 30.2% in the studied group are similar to those found in other groups from Poland and Europe. Pattern frequencies were transformed into numerical values after Wendt (table 7, fig. 1). There were found significant differences between arithmetic means of these values for males and females (table 8). Distributions of ridge number in males and females are presented on fig. 2. Table 9 supplies additional data in this respect. Statistically significant asymmetry in ridge number was found for fingers I and II in males and I, II, III in females. Sexual dimorphism in ridge number is clearly pronounced: except for finger II all intersexual differences were significant. Correlation coefficients for ridge numbers on homologous fingers of left and of right hand are high (table 10) pointing towards strong interrelationship between dermatoglyphics of antimeres.